An action theory-based electricity saving web portal for households with an interface to smart meters. (October 2016) - Mack, Birgit; Tampe-Mai, Karolin
Abstract: The reduction in electricity consumption by private households is an important factor in the process of enhancing the sustainability of energy infrastructures. The information architecture of an action theory-based smart meter web portal designed to facilitate electricity saving in private households is described with a focus on intervention techniques that support the transition from each stage of action planning to the next. Users are guided in their migration through the stages by the way information is structured. In order to address the gap between intention and action, the focus is on the support of the implementation of planned behavior. Highlights: A smart meter web portal was designed supporting electricity saving in households. Its information structure was designed against the backdrop of an action stage model. It guides the user in his or her migration through the action stages. It combines feedback with goal setting, social norms, saving tips, and commitment. It closes the gap between intention and action with implementation support techniques.